Structural and Optical Properties of BaWO4 Obtained by Fast Mechanochemical Treatment - Maria Gancheva; Reni Iordanova; Iovka Koseva; Iskra Piroeva; Petar Ivanov (Inorganics)
This work investigated the optical characteristics of BaWO4 nanoparticles that were produced through direct mechanochemical synthesis at varying speeds and times. This research expands upon our previous study. We demonstrated that the mechanochemical activation of the precursor of BaCO3 and WO3, at elevated milling speeds (850 rpm), facilitates the formation of tetragonal BaWO4 in a reduced reaction time. The final products were characterized by scanning electron microscopy (SEM), as well as Raman, infrared (IR), UV-Vis diffuse reflectance, and photoluminescence spectroscopies. The crystallite sizes and particles shapes were determined by X-ray diffraction and SEM analysis. Round particles with a size below 50 nm formed under different milling conditions. The Raman spectra of the synthesized samples confirmed the presence of a scheelite-type structure with the typical six distinct vibrational peaks. The symmetry of the structural WO4 groups was determined by IR spectroscopy. The absorption spectra of both samples exhibited intensive peaks at 210 nm, and the calculated optical band gaps of BaWO4 were 5.10 eV (3 h/500 rpm) and 5.24 eV (1 h/850 rpm). A strong (400 nm) and weak (465 nm) emission were observed for the BaWO4 that was obtained at a higher milling speed, while wider emission at 410 nm was visible for the BaWO4 that was prepared at a lower milling speed. The CIE coordinates of the mechanochemically synthesized BaWO4 were located within the blue area, exhibiting various positions.